The European Union and Public Health Emergencies: Expert Opinions on the Management of the First Wave of the COVID-19 Pandemic and Suggestions for Future Emergencies - Gontariuk, Marie; Krafft, Thomas; Rehbock, Cassandra; Townend, David; Van der Auwermeulen, Loth; Pilot, Eva (Frontiers in Public Health, 2021)
Objective: The first wave of the coronavirus SARS-COV-2 pandemic has revealed a fragmented governance within the European Union (EU) to tackle public health emergencies. This qualitative study aims: 1) to understand the current EU position within the field of public health emergencies taking the case of the COVID-19 as an example by comparing and contrasting experiences from EU institutions and experts from various EU Member States at the beginning of the pandemic; and, 2) to identify and to formulate future EU pandemic strategies and actions based on experts' opinions. Methods: Eighteen semi-structured interviews were conducted with public health experts from various European Member States and European Commission officials from May 2020 until August 2020. The transcripts were analyzed by Thematic Content Analysis (TCA), mainly a manifest content analysis. Results: This study demonstrated that the limited EU mandate in health hinders proper actions to prevent and tackle infectious disease outbreaks, such as the COVID-19 pandemic. The results showed that this limitation significantly impacted the ECDC, as the Member States' competence did not allow the agency to have more capacity. The European Commission has fulfilled its role of coordinating and supporting the Member States by facilitating networks and information exchange. However, EU intra- and inter-communication need further improvement. Although diverse EU instruments and mechanisms were found valid, their implementation needed to be faster and more efficient. The results pointed out that underlying political challenges in EU decision-making regarding health emergencies hinder the aligned response. It was stated that the Member States were not prepared, and due to the restriction of their mandate, EU institutions could not enforce binding guidelines. Additionally, the study explored future EU pandemic strategies and actions. Both, EU institutions and national experts suggested similar and clear recommendations regarding the ECDC, the investment, and future harmonized preparedness tools. Conclusion: The complex politics of public health at the EU level have led to the fragmentation of its governance for effective pandemic responses. This ongoing pandemic has shed light on the fragility of the political and structural systems in Europe in public health emergencies. Health should be of high importance in the political agenda, and robust health reforms at the local, regional, national, and EU levels are highly recommended.